Theory of the perception - MAKHLOUF, mokhtar (Journal of Human Sciences, 2006)
The subject deals with basic ideas connected to psychology of perception, and then, goes to a more general level of analysis which is directly related to kinds of Experiences needed to be used in our eroding environments. The starting point of this paper is to emphasize that ideas and conceptions of man are directly interwoven with materials, activities and social organizations